Shaking the Dust off the Markan Mission Discourse - Rogers, T. J. (Journal for the study of the New Testament, 2004)
The mission discourse in Mark has produced no exegetical consensus among scholars, particularly with regard to the list of items in vv. 8-9 and the dust-shaking gesture in v. 11. The author critiques the most commonly offered interpretations and argues that the pericope is best understood when read in the context of ancient hospitality norms, implied in v. 10. The list of items restricts the self-sufficiency of missionaries to the point of requiring them to receive the hospitality commanded in the following verse. Likewise, the dust-shaking is best understood as a testimony that their feet were not washed according to the customs of hospitality. The plausibility of this interpretation is then tested against the social-historical context of Christianity in the first century.